Screening and Agronomic Trait Association of Rice Germplasm for False Smut Resistance - Ravali, Somshetty; Basha, S. Ameer; Mohan, Y. Chandra; Babu, T. Kiran; Pushpavalli, S. N. C. V. L.; Pushpavalli, S. N. C. V. L.; Naik, B. Balaji (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during kharif, 2021 and 2022 (June–October) at the College Farm, College of Agriculture, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad, Telangana, India to study on screening of rice germplasm against false smut disease, caused by Ustilaginoidea virens, A total of 60 rice germplasm lines were evaluated for their reaction to false smut. Among these, 16 genotypes, namely Abhaya, Chittimuthyalu, HR 59, IET 23993, JGL 30090, MTU 1153, MTU 3626, MTU 4870, NDLR 7, Swarna, Tellahamsa, WGL 1272, PR 126, PR 127, PR 121, and RNR 11718, exhibited highly resistant reaction, whereas no genotype showed resistant reaction. Four genotypes (PR 124, MTU 1075, NLR 40065, and HR 12) showed moderately resistant reaction, 29 genotypes were moderately susceptible, 10 genotypes were susceptible, while TN 1 recorded a highly susceptible reaction. Genotypes with compact panicles exhibited higher disease incidence. Correlation analysis revealed a significant positive association between false smut incidence and the number of grains per panicle, while a significant negative correlation was observed with panicle length. Grain type also influenced disease incidence, with short slender grains showing the highest susceptibility, followed by medium slender, long bold, long slender, and short bold, while extra-long slender grains showed the least incidence. Cluster analysis based on plant characters and disease response grouped more than 65% of genotypes similarly, indicating a strong relationship between morphological traits and false smut resistance.